A critical appraisal of individual social capital in crisis response. Issue 2 (19th September 2021) - Morsut, Claudia; Kuran, Christian; Kruke, Bjørn Ivar; Nævestad, Tor‐Olav; Orru, Kati; Hansson, Sten
Abstract: While there is still a vast body of scholarly research in crisis and disaster management that considers social capital an asset for lessening negative impacts from crises, this paper investigates an underexplored aspect of social capital—its microlevel positive and negative instances in the crisis response—a quite neglected phase of the crisis management cycle when it comes to studying the role of social capital. To underline social capital's double‐edged aspects, this paper draws from the handful of studies that focus on individual social capital in crisis response, to systematize their findings according to bonding, bridging, and linking social capital and positive and negative impacts. In addition, the paper considers these findings to analyze the 2011 Utøya terrorist attack in Norway, to uncover new positive and negative effects of individual social capital, thus contributing to pushing the research agenda toward a more critical appraisal of individual social capital. 摘要: 尽管大量的危机和灾害管理学术研究认为，社会资本能作为一种优势用于减少危机的负面影响，但本文研究了一个关于社会资本的、有待探究的方面，即其在危机响应中发挥正负面作用的微观层面，就研究社会资本的作用而言，这是危机管理周期中特别被忽略的方面。为强调社会资本的双重作用，本文基于为数不多的研究（聚焦于危机响应中的个体社会资本），将研究发现根据整合型、桥接型、连结型社会资本以及正负面影响加以系统化。此外，本文衡量了研究发现，用于分析2011年挪威于特岛恐怖袭击，以期揭示个体社会资本的正负面效果，进而对"推动研究议程对个体社会资本进行更具批判性的评价"作贡献。 Resumen: Si bien todavía existe un vasto cuerpo de investigación académica en gestión de crisis y desastres que considera el capital social como un activo para disminuir los impactos negativos de las crisis, este documento investiga un aspecto poco explorado del capital social: sus instancias positivas y negativas a nivel micro en la respuesta a la crisis. una fase bastante descuidada del ciclo de gestión de crisis cuando se trata de estudiar el papel del capital social. Para subrayar los aspectos de doble filo del capital social, este documento se basa en un puñado de estudios que se centran en el capital social individual en respuesta a la crisis, para sistematizar sus hallazgos de acuerdo con la vinculación, vinculación y vinculación del capital social y los impactos positivos y negativos. Además, el documento considera estos hallazgos para analizar el ataque terrorista de Utøya en 2011 en Noruega, con el fin de descubrir nuevos efectos positivos y negativos del capital social individual, contribuyendo así a impulsar la agenda de investigación hacia una valoración más crítica del capital social individual.